28. Diagnostic and prognostic procedures in disorders of consciousness: Toward a SINC-SIRN consensus. Issue 12 (December 2017) - Estraneo, A.; Amantini, A.; Costa, P.; De Tanti, A.; Grippo, A.
Abstract : To date no national guidelines about diagnostic and prognostic evaluation of patients with disorders of consciousness (DoC) are available. As a consequence, diagnostic and prognostic procedures for DoC are extremely heterogeneous across clinical settings both in acute and chronic phases. The aim of this study is to plan a "SINC-SIRN" protocol on diagnostic and prognostic procedures as best practice and gold standard. Special Interest Groups (SIG) of SINC and SIRN, with complementary expertise in clinical and research in neurophysiology and rehabilitation, will cooperate in the following working steps: 1. Revision of scientific literature on diagnostic and prognostic procedures. 2. Elaboration of a "SINC-SIRN" protocol focused on the acute and post-acute/rehabilitative phases of care pathway. 3. Discussion and sharing within SINC and SIRN-SIG members. 4. Approval by SIRN and SINC executive committees. The preliminary diagnostic and prognostic protocol includes: 1. The Italian version of Coma Recovery Scale-Revised as a clinical tool. 2. Standard EEG. 3. Bilateral upper limb somatosensory evoked potentials. 4. Event-related potentials with detection of N100 and P300 cortical components. The integration of clinical and neurophysiological evaluation in the routine care from acute to chronic phase could provide useful diagnostic and prognostic information to guide management of patients with DoC.